(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
This article delves into the nuances of locomotive power, with a specific focus on both active and reactive components. The investigation of these components is imperative for gaining insights into the dynamic attributes of train operations. Through an extensive literature review, diverse viewpoints pertaining to active and reactive power within the context of locomotives will be scrutinized. The section on research methodology delineates the systematic approach employed for the analysis and quantification of these power components. Subsequently, the section on analysis and results provides a presentation of insights derived from empirical findings, elucidating the significance and ramifications of active and reactive elements in locomotive power. The conclusion succinctly synthesizes pivotal findings, accentuates the contributions of the study, and proposes potential avenues for further research within this domain.